The Effect of Coal Production, Domestic Market Obligation, Selling Price, Coal Reserves, and Mining Investment on Indonesia's Coal Export Realization - Trilaksana, Ahmad Raymond; Subiyantoro, Heru (Dinasti Publisher, 2026)
As the world's second-largest coal exporter, Indonesia faces complex dynamics in managing its coal export realizations amid domestic policy obligations and market fluctuations. This phenomenon is increasingly significant given coal's strategic role as a major source of state revenue and its position as a primary energy supplier to Asian emerging markets, particularly China and India. This study aims to analyze the determinants affecting Indonesia's coal export realizations. The research employs a quantitative approach using quarterly time-series data from 2014 to 2023, comprising 40 observations. The analytical methods utilized are the Vector Error Correction Model (VECM) to examine both short-term dynamics and long-term equilibrium relationships among variables. The independent variables examined include coal production volume, domestic market obligation (DMO), selling price, coal reserves, and mineral and coal sector investment, with coal export realization as the dependent variable. The findings reveal that simultaneously, all independent variables significantly influence coal export realizations. Partially, coal production, selling price, coal reserves, and investment demonstrate significant positive effects on export realizations. Conversely, domestic market obligation shows a significant negative effect on Indonesia's coal export realizations, indicating that mandatory domestic supply requirements constrain export volumes.